Semen collection in Rusa timorensis under general anaesthesia by using Ketamine-Xylazine: clinical study - Wan Jaafar, Wan Nor Fitri; Haron, Abd Wahid; Abdullah Jesse, Faez Firdaus; Zainal Abidin, Siti Aimi Sarah; Mohd Lila, Mohd Azmi; Rashid, Muhammad Azrolharith; Kamarudin, Zubaidah; Yawah, Donny; Zulhizri, Ahmad; Che Amat, Azlan; Yap, Keng Chee (Mosul University, 2021)
There is a scarcity of information for a reliable and safe protocol for semen collection in R. timorensis. The induction of general anesthesia by Ketamine-Xylazine in both intravenous and intramuscular routes provides valuable information for the practicality of the procedure. Five healthy and matured Rusa timorensisstags, aged more than 3 years, weighing an average of 68.5 ± 2.4 kg were selected for this experiment. General anaesthesia was conducted by using a combination of Ketamine and Xylazine at the dosage of 2mg/kg, and 1mg/kg respectively in both intramuscular and intravenous routes. The procedure was performed from April to November 2012 resulting in 30 collections. The physiological parameters included were respiratory rate, heart rate and temperature before, during and post-procedure. The onset, recovery and total time are significantly different between IV and IM route at 5.13 ± 0.88 min, 7.47 ± 1.61 min, 18.67 ± 1.47 min, and 11.67 ± 1.44 min, 11.73 ± 1.03 min and, 29.07 ± 4.01 min respectively. Meanwhile, there is no significant difference in the duration time of anesthesia between IV and IM route at 15.27 ± 3.03 min and 17.40 ± 3.55 min respectively. Both routes provide the same success rate and yield the same semen quality, however, the intravenous route is desirable due to fast induction and recovery time. General anaesthesia is integral for the restraining of wild cervidae, intravenous route of drug administration should be considered for semen collection in Rusa deer.